Progress in measurement of retinal vascular caliber. Review - N. S. Semenova; V. S. Akopyan; A. S. Rodin (Oftalʹmologiâ)
this review presented advances in computer-assisted methods of retinal vessels caliber assessment. Current mathematical models and associated problems are discussed.